CAMBIOS HISTOMETRICOS DEL EPITELIO DE LA MUCOSA PALATINA EN PACIENTES PORTADORES DE PROTESIS COMPLETA - Watanabe Velásquez, Romel Armando (1999)
With the purpose to observe the variations the dimensions of the eptely and the caver of the cornea, as well as the grade of querationation of the tipper mucous for the use of complete prothesys. Biopsip of tippermucous were done before the work and 60 daip after the installation of the complete prothesys the samples of the biopsip were fixed in metodo from and colouned urtle Hematoxilina and acido peryodico. The measurem were alone, using a micrometric ocular and the results were subject to analipsis statisteis, observing the follo wing a) Wilte the use of complete pro thesey a reduction of the thi cknessof epitely produced and also of the cave of the cave of the cornea of the tipper mucous, with no significance stadistically according the proof of student (p 0.5). b) The use of complete prothesys produces a tendencice of paraqueratinization of the tipper mucous, with no significances according to the prof chi cuadrado (p 0.05). c) These changes are part of the process of adaption of the tipper mucous befocccre the use of complete prothesys.